Scheduling on transportation for industrialized building systems - Foong, Kok Li (2006)
Now, the construction is facing the challenges from the four main aspects, which are quality, cost, time and safety. However, by implementing the industrialized building system (IBS), all those challenges can be faced easily. In this study, double storey shop houses will be used as a model to illustrate the management of IBS transportation for fabricators. Besides, the number of trucks required each day will be discussed here based on proper scheduling using project management software. Other than that, this study focuses on the scheduling by optimization. This project highlights a proper management of the trucks used in the delivery of IBS components for construction.